Variasi Verba “Memasak” Dalam Bahasa Bali - Ni Luh Putu Puspita Agustini (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
This paper describes the meaning of the verb cook in Balinese based on the theory of Natural Semantic Metalanguage. This research is to obtain a comprehensive meaning configuration of the lexical verb "cook" in Balinese. The method used in this research is descriptive-qualitative method by following the following steps: data classification, analyzing the semantic structure of the verb “cook”, and describing the components obtained to produce a configuration of meaning about special features, especially applying paraphrasing. Based on the analysis, it was found that the verb "cook" in Balinese can be expressed in several lexicon, namely: "ngukus, nunu, nyanyah, lablab, ngoreng, nguling, ngadon, ngurab, ngaru,".